2020
DOI: 10.3892/ol.2020.12341
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA SNHG9 inhibits ovarian cancer progression by sponging microRNA‑214‑5p

Abstract: Ovarian cancer ranks 7th among the most common cancer types affecting women worldwide. A number of studies have confirmed that multiple long non-coding RNAs participate in the occurrence and progression of ovarian cancer. Small nucleolar RNA host gene 9 (SNHG9) serves a role in the progression of glioblastoma and pancreatic cancer. However, the specific biological function of SNHG9 in ovarian cancer has not yet been fully investigated. The present study aimed to determine the biological role and potential mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…SNHG9 is a lncRNA whose coding gene is located on chromosome 17 and has a total length of approximately 416 base pairs. It was found to be associated with the development and progression of various cancers, including pancreatic cancer, glioblastoma, lung cancer, and ovarian cancer ( Zhang et al, 2018 ; Lin et al, 2020 ; Chen et al, 2021 ; Wang et al, 2022 ). To date, there are limited investigations on SNHG9 in EV-D68 infection.…”
Section: Discussionmentioning
confidence: 99%
“…SNHG9 is a lncRNA whose coding gene is located on chromosome 17 and has a total length of approximately 416 base pairs. It was found to be associated with the development and progression of various cancers, including pancreatic cancer, glioblastoma, lung cancer, and ovarian cancer ( Zhang et al, 2018 ; Lin et al, 2020 ; Chen et al, 2021 ; Wang et al, 2022 ). To date, there are limited investigations on SNHG9 in EV-D68 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has suggested that the SNHG9 may serve a role in multiple types of cancer 12, 17–19 . For instance, SNHG9 was identified as a prognostic marker for PC.…”
Section: Discussionmentioning
confidence: 99%
“…different cell processes such as cell migration, growth, invasion, apoptosis, and differentiation in OC (Wang et al, 2019 ). For example, SNHG9 was shown to serve as an anticancer biomarker by regulating miR-214-5p (Chen et al, 2021 ). LINC01969 was confirmed to be a cancer-promoting biological marker via the miR-144-5p / LARP1 axis (Chen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%